2012
DOI: 10.1097/jto.0b013e318240ca0d
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MET Gene Copy Number by Silver In Situ Hybridization and Protein Expression by Immunohistochemistry in Non-small Cell Lung Cancer

Abstract: Purpose The MET receptor is involved in the pathogenesis and progression of non-small-cell lung cancer (NSCLC). Clinical trials with MET inhibitors in NSCLC are planned with patient selection based on immunohistochemistry (IHC) and/or gene copy number assessment. Therefore, a detailed understanding of relationship between these markers and prognosis is essential. Methods This study included tumors from 189 NSCLC patients who underwent pulmonary resection (median follow-up 5.3 years). MET expression was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
111
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 25 publications
(42 reference statements)
15
111
0
2
Order By: Relevance
“…Interestingly, the first report from Glokhova and colleagues (33) demonstrated that gene copy number increase was associated with upregulation of MET expression. This observation is not limited to kidney cancer: similar correlations between MET gene copy number and protein expression level measured by immunohistochemistry have also been reported in nonsmall cell lung cancer (34). Previous cytologic reports identified chromosome 7 trisomy as a common feature of pRCC (11).…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, the first report from Glokhova and colleagues (33) demonstrated that gene copy number increase was associated with upregulation of MET expression. This observation is not limited to kidney cancer: similar correlations between MET gene copy number and protein expression level measured by immunohistochemistry have also been reported in nonsmall cell lung cancer (34). Previous cytologic reports identified chromosome 7 trisomy as a common feature of pRCC (11).…”
Section: Discussionsupporting
confidence: 51%
“…MET amplification has been classified by using MET:CEP7 ratio as low (!1.8 to 2.2), intermediate (>2.2 to <5), and high (!5). 131 Other…”
Section: Lindeman Et Al 140mentioning
confidence: 99%
“…[53][54][55] Phase 2 studies of combined erlotinib and Met inhibition using a monovalent anti-Met receptor antibody (MetMAb) have shown some benefit in patients with Met protein overexpression by immunohistochemistry 56 ; phase 3 trials of combined Met and EGFR inhibition are now underway. 57 MET gene copy number and protein expression are significantly correlated 58,59 ; however, in exceptional cases, strong Met protein expression may be seen in the absence of MET copy number gain. 60 To date, the best biomarker for assessing Met activation status has not been established; indeed the definition of positivity based on expression level or copy number is still a matter of debate and will likely not be resolved until larger studies of outcomes following treatment with Met-targeted agents come to fruition.…”
Section: Mechanisms Of Resistance To Egfr Inhibitorsmentioning
confidence: 99%